Factors Affecting the Students' Choice of a Major at King Abdulaziz University (Journal of the College of Education for Women, 2022)
The present study aimed at examining the factors that affect the choice of A major among a sample of BA fe(male) students at the levels 3-8 in King Abdulaziz University (KAU), in Jeddah, Saudi Arabia. To meet this objective, a descriptive survey method was used together with a questionnaire that consisted of 4 axes to answer the central question: What are the factors affecting the choice of a major at the university? Results have shown that the item that measured the students’ ability to choose the major ranked (First); it was concerned with the effect on the students' choice of his/her major in the university. On the last position and with respect to this effect came the professional tendencies and desires. Results have also shown that there were other differences of a statistical significance in favor of a literary major on the four axes of the questionnaire. Besides, there were no differences between the two sexes regarding the choice of a university major. The study has recommended the need for boosting the role of students' awareness, and holding workshops and cultural courses after joining college, as well as introducing majors, their fields and the application of a professional tendency scale in the preparatory stage in the university.